(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Young entrepreneurs face significant barriers when trying to get access to funding fromventure capital sources. In order to attract the attention and funding of venture capitalists, companyowners must provide compelling business plans. To this end, the company takes into account theinvestment requirements of venture capital firms. Without a doubt, entrepreneurs place a high value oninvestment criteria however, it is also important to investigate which investment criteria is moreimportant than others, so that entrepreneurs can prioritize and analyze the most crucial criteria. Thepurpose of this research is to identify the variables andor factors most valued by India’s venture capitalproviders when making investment decisions. In this paper discuss the criteria and variables ofhierarchy of investment.